Pendampingan Penyusunan Laporan Keuangan Berbasis Digital untuk Meningkatkan Akses Permodalan UMKM Gerakan Pemuda Ansor di Pagedangan Tangerang - Syakhrial Syakhrial; Baliyah Munadjat; Susilawati Susilawati (Jurnal PKM Manajemen Bisnis, 2026)
This community service program (PKM) addresses the limited capacity of UMKM members of Gerakan Pemuda Ansor in Pagedangan, Tangerang, in preparing digital financial reports that are essential for improving access to external funding. The objective of this activity is to enhance participants’ understanding and skills in preparing digital-based financial statements to support better access to capital for MSMEs. The PKM was conducted at Balai Desa Cicalengka, Pagedangan District, Tangerang Regency on 19 May 2026 by three lecturers from Universitas Pamulang, involving 32 participants from Gerakan Pemuda Ansor. Activities were implemented through material presentations, hands-on practice, group discussions, and question-and-answer sessions, following preparation, implementation, and reporting stages. The results of the program show an increase in participants’ understanding of digital accounting systems and their ability to compile more structured and transparent financial reports using simple digital tools. This improvement is expected to strengthen the financial governance of MSMEs under Gerakan Pemuda Ansor and facilitate greater access to banking institutions and other funding sources. Overall, the PKM contributes to sustainable capacity building for MSME actors through digital financial literacy and practical reporting skills and supports long-term economic resilience within the community through continuous mentoring and follow-up assistance activities in a structured manner.